Darwin’s finches in human-altered environments sing common song types and are more aggressive - Colombelli-Négrel, Diane; Akçay, Çağlar; Kleindorfer, Sonia (Frontiers in Ecology and Evolution, 2023)
Human-altered landscapes may act as an environmental filter benefiting species or individuals with specific sets of capacities or behaviours. Yet the effects of human activity on culturally transmitted traits in animals are still poorly understood. Combining song recordings and simulated territory intrusions, we investigated whether songs (a cultural trait) and aggressiveness (a personality trait) in small ground finches (Geospiza fuliginosa) differed along a gradient of human activity levels (high-low-high) spanning two habitats with contrasting levels of rainfall (arid lowlands, humid highlands). We found that more common syllable types were more prevalent in arid lowland sites and at sites with high human activity. The number of syllables per song, song duration, song tempo and song rhythmicity did not differ across habitats or levels of human activity. During simulated territorial intrusions, small ground finches living in areas with higher levels of human activity and in the arid lowlands (regardless of human activity) showed the strongest aggressive response compared to those living in areas with lower levels of human activity or in the humid highlands. Thus, prevalence of aggression and syllable commonness correlated with each other across sites. Our results support the idea that resource distribution and human-impacted environments may select jointly for specific behavioural phenotypes such as aggression as well as common cultural traits.